THE INSTRUCTIONAL LEADERSHIP OF SCHOOL PRINCIPALS IN IMPROVING TEACHER PERFORMANCE - Andriani Sariwardani; Nura’syiah; Umalihayati; Suandi Silalahi (Cakrawala Pedagogik, 2025)
This study examines the role of principal instructional leadership in improving teacher performance. The research method used is descriptive qualitative. The subjects of this study were 26 principals at Elementary Schools in Pontang District, Serang Regency, Banten. The data collection techniques used were interviews and observations. The results of this study illustrate that principals can manage schools to improve teacher teaching performance with models and strategies that are built in order to realize organizational goals. Dimensions or indicators of instructional leadership that can affect teacher teaching performance are developing missions and goals for improving school curriculum, developing professional learning communities, developing work environments and promoting academic learning climates.